FORMATION OF LEGAL COMPETENCE OF FUTURE TEACHERS OF HISTORICAL AND CIVIC EDUCATIONAL SUBJECTS IN THE CONTEXT OF NOVELS OF EDUCATIONAL LEGISLATION - Zalij, Tamara (SWorld-Ger Conference proceedings, 2024)
The article traces the features of the formation of legal competence of future teachers of historical and civic education. It is indicated that in the conditions of the European progress of the state, changes in educational legislation, active discussion